Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/micr.30333
|View full text |Cite
|
Sign up to set email alerts
|

The facial artery perforator flap for intraoral reconstruction of a mouth floor defect

Abstract: Facial artery perforator flaps have been recently reported by different authors for perioral, nasal alar and cheek defects, but not for intraoral reconstruction. We have extended the use of the facial artery perforator flap in a 56-year-old man with a squamous cell carcinoma of left mouth floor, who was submitted to tumor resection with marginal mandibulectomy and left supraomohyoid neck dissection. The flap was designed according to the size of the defect (5 × 3 cm), centered on the perforator to create a sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it is imperative to recognize that free flap surgery may be contraindicated in cases where patients are unable to endure prolonged operative times due to underlying comorbidities, such as cardiopulmonary conditions, cardiac issues, or impaired renal function [2,3,10]. In such instances, when feasible, local flap techniques may present a suitable alternative, particularly for small-to moderate-sized intraoral defects [1][2][3][4][5][11][12][13][14][15][16][17]. In a previous study, we reported a successful case involving the use of a single-stage peninsular-shaped lateral tongue flap (pLTF) for reconstructing an intraoral defect following tumor resection in the buccal area, which encompassed the retromolar trigone (RMT) region [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is imperative to recognize that free flap surgery may be contraindicated in cases where patients are unable to endure prolonged operative times due to underlying comorbidities, such as cardiopulmonary conditions, cardiac issues, or impaired renal function [2,3,10]. In such instances, when feasible, local flap techniques may present a suitable alternative, particularly for small-to moderate-sized intraoral defects [1][2][3][4][5][11][12][13][14][15][16][17]. In a previous study, we reported a successful case involving the use of a single-stage peninsular-shaped lateral tongue flap (pLTF) for reconstructing an intraoral defect following tumor resection in the buccal area, which encompassed the retromolar trigone (RMT) region [2].…”
Section: Introductionmentioning
confidence: 99%